Conversion of Biomass to Organic Acids by Liquefaction Reactions Under Subcritical Conditions - Yüksel Özşen, Aslı (Frontiers in Chemistry, 2020)
Recently, liquefaction of biomass in subcritical water to convert it into value-added substances has been broadly attracting attention. However, there is a gap in literature about the levulinic acid, which is a high worth substance, production from biomass using subcritical water. As a green chemistry approach, decomposition of biomass could be obtained using subcritical water effectively. In this case, water uses as a solvent so that it gives a possibility to take place a reaction for the decomposition of biomass. Subcritical water, which liquid water and its temperature is higher than the normal boiling point of water, has higher ion product as well as higher concentrations of H+ and OH− ions. Additionally, it has high diffusivity, low viscosity and much lower dielectric constant. For instance, whereas dielectric constant of subcritical water is 80 at 298 K, it is 2 at 673 K. The point of this research paper is to assess the impacts of different reaction parameters on cellulose conversion as the principle segment of lignocellulosic biomasses for the production of value-added chemicals, particularly levulinic acid. Hazelnut shell waste was chosen as model biomass since hazelnut is a standout amongst the most cultivated agricultural crops in Turkey. Besides, Turkey provide 70% of the world's total hazelnut production. It was found that as reaction temperature increases, a considerable improvement on the amount of formed levulinic acid and conversion of hazelnut shell was observed. For instance, when the reaction temperature, time and acid concentration were 280°C, 120 min and 50 mM, respectively, levulinic acid yield and conversion of hazelnut shell were found as 13.05 and 65.40%, respectively. Addition of H2SO4 enhanced the production of levulinic acid from waste hazelnut shell. Another method which is hybrid process could be used to produce value-added chemicals from lignocellulosic biomass. Hybrid process basically combines hydrolysis and electrolysis in subcritical water. Subcritical water has much lower dielectric constant than liquid water at ambient temperature. So, it was claimed that if constant current was applied to the reaction medium through specially designed electrodes in subcritical water environment, electrolysis could alter the hydrolysis reaction of cellulose in a way of protonation of intra-and inter-molecular hydrogen bonding around anode and as a result electrolysis in subcritical water could decrease necessary thermal energy to hydrolyze the β(1–4) glycosidic linkage. Therefore, we developed a green hybrid process by combining hydrolysis and electrolysis in subcritical water without using any toxic, organic solvents and catalyst. Effects of especially applied current and temperature on the product distribution and conversions of cellulose were revealed and hydrothermal electrolysis reaction pathway of cellulose was proposed. The significance of the interaction indicated that, applied voltage had major impact on cellulose hydrolysis. Maximum cellulose conversion (82%) was achieved at 230°C and 180 min of reaction time in 25 mM of H2SO4. Application of 8.0 V of applied voltage to the reaction medium at reaction temperature of 230°C increased the TOC conversion (50.3%) with acid concentration of 25 mM in comparison with current-free experiments. Thus, the idea of electrochemically generated acid layer due to the dissociation of water around anode is supported. As future perspective, the output of the study gave an idea about converting cellulose and various biomass wastes, which may have high cellulose, content and led the way in obtaining valuable chemicals from no utilized real biomass sources such as hazelnut shell waste. The studies with other biomasses are undergoing.